Production and quality evaluation of canned tomato paste prepared from pre-treated sun-dried tomato slices and leather (Salsadeen) - Mohamed Salih Abd Allah, Hagir; Elmubarak, Abd Alla; Basheer, Babiker (Libyan Journal of Science &Technology, 2022)
The aim of this study was to preparing canned tomato paste from pretreated sun-dried tomato slices and leather (Salsadeen). Fresh, mature and ripe tomato sample (Lycopersicun esculentum) purchased from Omdurman local market was used in this study. The bulk of tomatoes were divided into three portions used for preparation of fresh tomato paste, sun-dried tomato slices and leather (Salsadeen). The portion used to prepare pretreated sun-dried tomato slices was divided into three groups, the first was dipped in 10% sodium chloride (salt solution) for 3 minutes, the second was dipped in 10% sodium chloride (salt) and 0.9% sodium metabisulphite solution for 3 minutes, the last was left un treated. The tomato pulp used to prepare tomato leather (Salsadeen) was divided into two portions one was treated with 1.5% sodium metabisulphite and the other was left untreated. Treated tomato slices and pulp was sun-dried for 24 hours and the experiment was replicated 3 times. Tomato paste was prepared from reconstituted sun-dried tomato slices and leather (Salsadeen) as well as from fresh tomato pulp. The quality characteristics (Total Soluble Solids, color, Titerable Acidity, pH, Salt content, Viscosity and panel test) of tomato paste prepared from fresh and pre-treated sun-dried tomato slices and leather (salsadeen) was evaluated in this study. Results indicated that tomato paste prepared from dried tomato slices dipped in 10% sodium chloride and 0.9% sodium metabisulphite solution was superior in quality except in salt content. The main recommendations of this study were that dried tomato slices and leather can be used to prepare tomato paste after reconstitution, and it will be of interest to get advantages of tomato during the season to prepare dried tomato slices or leather and use it off-season to prepare tomato paste. The dried tomato slices or leather (Salsadeen) must pretreat to prepare good quality tomato paste. Salt content in dipped solution of tomato slices must be decreased.